Advocacy for the Rights of Visually Impaired in Voting at Polling Stations: : Advocacy for the Rights of Visually Impaired in Voting at Polling Stations: Advocacy Study of the Persatuan Tunanetra Indonesia DKI Jakarta in the 2019 Election - Cristiani, Lea; Ghofur, Abdul (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Election practices for people with visual disabilities are still not implemented ideally. Various problems occur when people with visual disabilities vote at polling stations. This research aims to analyze how the advocacy carried out by Pertuni DKI Jakarta is related to the rights of blind people to vote at polling stations in the 2019 Election. Participating in elections is the right of every Indonesian citizen, including visually impaired. The existence of political rights to vote at polling stations for people with visual disabilities has been regulated in statutory regulations. However, fulfilling the political rights of people with visual disabilities is still considered inadequate, so it is necessary to fulfill these rights through disability organizations, namely Persatuan Tunanetra Indonesia (Pertuni). It can be done by conducting advocacy. To support this research, researchers used qualitative methods to interpret and analyze data in more depth from a broad and subjective perspective. This research also has a novelty in that it looks at advocacy for the rights of people with disabilities from the perspective of blind people in the Pertuni organization. As a result, this research found that the advocacy carried out by Pertuni was related to the rights of people with disabilities to vote at polling stations in the form of joint hearings with the Electoral Commission